PENGARUH EMIC VIEW TERHADAP PENETAPAN KELAYAKAN LINGKUNGAN RENCANA PEMBANGUNAN JAWA-BALI - Endang Susilowati; Sukriyah Kustanti Moerad; Zaenal Arifin (Institut Teknologi Sepuluh Nopember, 2018)
Bali Island as a domestic and international tourist destination object needs a large scale capacity of electricity supply. For this reason, PT. PLN (Persero) Main Unit of Java-Bali Connection Development will construct The SUTET 500 kV from GISTET Paiton to GISTET Antosari and SUTT 150 kV from GI Antosari to GI Kapal. This transmission connection will across paddy field, dry field, hill, sea, conservation area in Baluran-East Java and West Bali National Park (TNBB). The route is as long as ± 239,68 km across east part of East Java and west part of Bali Island. Based on Regulation of Environmental Ministry No.05, Year 2012, the development plan must prepare an environmental document for getting environmental feasibility that is used for stipulating environmental permit. The development plan for public interest carried out by government, such as electricity plan or electricity supply, is often failed to be implemented because of the problem on stipulating of environmental permit. This is caused by the environmental feasibility that it can not be stipulated by technical and commission assessment team of environmental document based on 10 criteria of environmental feasibility.( Regulation of Environmental Ministry No.16, Year 2012). Mainly the environmental feasibility no 7, that is social-economic and social-culture in the form of emic view of community of the development plan. Based on this background, the research on The Influence of Emic View through Stipulation of Environmental Feasibility of Development Plan Jawa Bali Crossing (JBC)-SUTET 500 kV Paiton-Antosari dan SUTT 150 kV Antosari-Kapal, is conducted. This is a descriptive analysis research, with 100 respondents selected by purposive random sampling and analyzed by interpretative, causa-logical, descriptive and reflective and it is conducted in Sumber Klampok village-Gerogak District, Buleleng Regency-Bali Province. The assessment of the environmental document resulted that most of the ten criteria fulfill the environmental feasibility, except one criteria, that is emic view of community on religion, but the feasibility of the environmental document can not be stipulated by technical and commission assessment team of environmental document, even though perception and attitude of majority respondent are very significant (83,00%) and positive through the development plan. The most respondent’s hope (81,67%) is that the development plan soon to be implemented. It is resulted that the influence of emic view is very significant through environmental feasibility stipulation for issuing environmental permit.